Dinamika Urban Sufisme dan Salafi di Era Digital: Implikasinya Terhadap Pergeseran Tren Halal Lifestyle Masyarakat Perkotaan - Muh Tabran (Journal of Islamic Economy and Business (JIsEB), 2024)
This study aims to comparatively examine the cyber adaptation strategies adopted by Urban Sufism and Salafi movements, and to analyze how the dynamics of digital religiosity from these two contrasting poles of thought implicate the shifting trends of halal lifestyle among urban societies. This study utilizes a qualitative approach with a descriptive-analytical library research method. The framework of digital sociology integrated with the perspective of Islamic economic sociology is employed as the formal framework. Primary and secondary data were gathered through digital text documentation techniques and rigorously analyzed using content analysis alongside hermeneutic-textual methods. The results demonstrate that digital Urban Sufism successfully promotes the visualization of inclusive piety based on spiritual aesthetics, triggering trends in the modest fashion industry (Sufi-Chic), paid spiritual literacy, and halal tourism. Conversely, the Salafi cyber movement acts as a strict gatekeeper of standardization through the hijrah narrative, driving an explosion in the collective syar'i clothing market, the acceleration of riba-free Islamic finance, and the rise of community-based herbal industries. This study offers a significant novelty by bridging contemporary cyber religiosity with market economic structures through the lens of religious commodification. It addresses a critical research gap by avoiding a fragmented analysis of Sufi and Salafi movements, instead comparing them in parallel to reveal how they influence the polarization of taste cultures among urban Muslim consumers.